Migraines, Obesity, and Pregnancy: Who Is the Villain and Who Is the Victim? - Milan Lackovic; Sladjana Mihajlovic; Jovana Kuzmanovic Pficer; Ivan Hristov; Zagorka Milovanovic; Ivona Jovanovic; Dejan Nikolic (Life, 2025)
Introduction: Migraines are a prevalent neurovascular disorder that affects more than a billion people worldwide. Even though both women and men are affected by this neurological disorder, migraines are primarily recognized as a women’s health disruption factor. Pregnancy leads to significant hormonal changes, including a rise in estrogen, progesterone, and endogeny opioid levels, and, therefore, it can affect the course of migraines. Women dealing with migraines often experience migraine symptom reduction during the course of pregnancy, but in the setting of increased maternal body mass index and obesity, this common pattern may be altered. Due to the complexity of the interplay between pregnancy, obesity, and migraines, all mediated by hormonal changes, the aim of our study is to try to unravel the impact of migraines and obesity on maternal health and pregnancy outcomes. Methods: This study included 350 subjects who have suffered at least one migraine attack three months preceding pregnancy, or at any point during the course of pregnancy. Initially, the study subjects were divided into two groups. The first group included women suffering from migraines before pregnancy, but not during the course of pregnancy, and the other group included all subjects who remained symptomatic during the course of pregnancy or had a first migraine attack during their pregnancy. Further comparisons were made based on the patients’ BMI values, and correlations were made between the obese and non-obese study subjects. Results: Higher parity (p = 0.005), obesity (p = 0.005), earlier age of migraine onset (p = 0.004), and gestational diabetes mellitus (p = 0.004) were statistically significant predictors for migraine symptom persistence during pregnancy. Obese pregnant women were more likely to experience migraine intensity and frequency persistence during pregnancy (p < 0.001 and p < 0.001, respectively). They sought magnesium treatment more often (p < 0.001), but this had a modest therapeutic effect compared to non-obese pregnant women (p < 0.001). A diagnosis of hypertensive disorder of pregnancy and gestational diabetes mellitus was also more frequently established in the group of obese pregnant women (p = 0.002 and p < 0.001, respectively). Conclusions: Pregnancy induces substantial physiological changes that can both alleviate and exacerbate migraine symptoms. Obesity is a modifiable risk factor that not only may increase the intensity and frequency of migraine symptoms, but may also compromise pregnancy course and outcome. The co-occurrence of migraines and obesity during pregnancy may amplify health risks for the mother and fetus, including heightened susceptibility to gestational diabetes mellitus. Future research should prioritize focusing on better understanding the causal relationships between pregnancy, migraines, and obesity and providing treatment strategies the home in on weight management and the control of migraine symptoms and associated comorbidities.